High-Throughput Sequencing-Based Identification of Arabidopsis miRNAs Induced by Phytophthora capsici Infection - Zhu, Xiaoguo; He, Shidan; Fang, Di; Guo, Liang; Zhou, Xiaoyi; Guo, Yushuang; Gao, Lei; Qiao, Yongli (Frontiers in Microbiology, 2020)
MicroRNAs (miRNAs) are a group of small non-coding endogenous RNAs. In plants, miRNAs play vital functions in regulating growth, development, and stress response. However, the role of miRNAs in Arabidopsis-Phytophthora capsici (P. capsici) model pathosystem is poorly understood. Here, we used a high-throughput sequencing approach to identify pathogen-responsive miRNAs using 15 small RNA (sRNA) libraries prepared from Arabidopsis thaliana leaves collected at 0, 3, 6, 12, and 24 h post-inoculation with P. capsici. A total of 293 known miRNAs and 6 potential novel sRNAs (miRNAs or siRNAs) were identified, of which 99 miRNAs were differentially expressed at four different infection stages. To verify the reliability of sRNA-seq results, we investigated the expression of five sRNAs upregulated throughout the four infection stages and their potential target genes using northern blot analysis and/or stem-loop quantitative real-time polymerase chain reaction (qRT-PCR). Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses revealed that the potential target genes of the differentially expressed miRNAs, both conserved and novel, were significantly enriched in pathways such as starch and sugar metabolism, spliceosome, and plant-pathogen interaction, indicating that the splicing machinery and pathogenesis-related (PR) proteins play important roles in the response to P. capsici infection. Taken together, these results provide novel insights into the molecular mechanisms of pathogenesis by P. capsici. Additionally, these results will serve as a strong foundation for further in-depth analysis of miRNAs involved in the resistance to Phytophthora species in other crops.